Utilization of a Conidia-Deficient Mutant to Study Sexual Development in Fusarium graminearum - Son, Hokyoung; Lim, Jae Yun; Lee, Yoonji; Lee, Yin-Won (PLOS ONE, 2016)
Transcriptome analysis is a widely used approach to study the molecular mechanisms underlying development and the responses of fungi to environmental cues. However, it is difficult to obtain cells with a homogeneous status from the sexually-induced culture of the plant pathogenic fungus Fusarium graminearum. In this study, we provided phenotypic and genetic evidence to show that the current conditions applied for perithecia induction inevitably highly induced asexual sporulation in this fungus. We also found that hundreds of genes under the control of the conidiation-specific gene ABAA were unnecessarily upregulated after perithecia induction. Deletion of ABAA specifically blocked conidia production in both the wild-type strain and sexually-defective mutants during sexual development. Taken together, our results suggest that the abaA strain could be used as a background strain for studies of the initial stages of perithecia production in F. graminearum. Further comparative transcriptome analysis between the abaA mutant and the sexually-defective transcription factor mutant carrying the ABAA deletion would contribute to the construction of the genetic networks involved in perithecia development in F. graminearum.